Comparative Study of Islamic Law and Western Law in Criminal Law and Justice Systems - Dr. Mazhar Hussain,; Dr. Muhammad Ismail,; Dr. Nabeela Falak,; Dr. Sardar Ali,; Dr. Atiq Ur Rahman Qureshi,; Adil Bajwa, Lecturer, (Al-Qanṭara, 2023)
Islamic law or Sharia law is characterized by a significant emphasis on moral principles and the guidance provided by a divine source. It categorizes criminal offenses into two distinct categories: Hudud, which are fixed offenses, and Tazir, which are discretionary offenses. Each category is associated with its own set of sanctions. The pursuit of justice in Islamic law is characterized by a comprehensive strategy aimed at reconciling parties and reinstating social order. On the other hand, Western law is derived from secular philosophies that prioritize reason, individual rights, and the principle of legal governance. Criminal offenses are classified according to their level of seriousness, with a particular focus on factors such as proof, intent, and the extent of harm caused. The fundamental principles of justice administration in Western legal systems are upheld by the provision of procedural rights, which include the presumption of innocence and the right to a fair trial. The comparative analysis demonstrates instances of convergence, including a mutual dedication to principles of justice and equity, alongside the impact of global human rights norms on both systems. Nevertheless, notable distinctions can be observed in the origins of legal systems, intellectual foundations, and methods of administering penalties. Islamic law incorporates religious precepts into its legal structure, whereas Western law prioritizes secular reasoning and human autonomy. These disparities give rise to divergent viewpoints about the concept of punishment, regulations pertaining to evidence, and the equilibrium between religious principles and societal standards. This research study presents a complete comparison analysis of Islamic law and Western law in the context of criminal law and justice systems. The objective of this study is to examine the core principles, methodologies, and implementations of these two legal frameworks, with a focus on identifying their commonalities, disparities, and potential points of intersection. The investigation contains fundamental elements, including the conceptualization of crime in Islamic law and Western law, as well as the elucidation of the justice systems within both legal frameworks. This study enhances our comprehension of distinct legal viewpoints by examining the complex dynamics between Islamic and Western legal systems.